Back Cover: Bubble‐pen lithography: Fundamentals and applications. Issue 4 (24th August 2022) - Kollipara, Pavana Siddhartha; Mahendra, Ritvik; Li, Jingang; Zheng, Yuebing
Abstract : Bubble‐pen lithography exploits laser heating for microbubble generation to attract and pattern diverse kinds of materials at the microscale or nanoscale resolution. Zheng and co‐workers discuss theoretical and experimental advances in bubble‐pen lithography and its applications in the fields of displays, biological and chemical detection, disease diagnosis, and nanoalloy synthesis (e189 ).